Indonesian Uncertainty on Tourism Components in the New Normal Period and the Ability to Travel Soon - Imam Nur Hakim; Chamma Fitri Putri Pradjwalita Koesfardani; I Dewa Gede Richard Alan Amory (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
When the COVID-19 pandemic hit Indonesia, one of the most-impacted industries was its tourism sector. After the government developed various transmission prevention policies, a press release from the Indonesian president in May 2020 established the new normal terms. These new terms sought to allow Indonesians to return to travel as soon as possible with several protocols in place. However, the post-pandemic situation has made some Indonesians feel an intolerance towards the uncertainty of changes in the tourism component. Through a descriptive quantitative approach using the theory of Intolerance of Uncertainty (IU), this study aimed to determine what Indonesians feel about uncertainty, how they feel about it, and how to reduce these feelings in Camilleri’s five components of tourism. The results showed that Indonesians feel uncertainty in every component of tourist destinations, with accommodation being the most significant factor, followed by financial, protocol readiness, and health factors, particularly the threat of contracting the virus and the number of cases. Therefore, appropriate handling to eliminate the number of affected cases and the uncertainty of crowds in the destination can significantly contribute to creating the ideal situation awaited by most Indonesians before they decide to return to travel.